Correction of an acid soil using the base saturation method and influence on chemical parameters - Jose Carlos Pintro; Maicon Dieison Tescaro (Acta Scientiarum. Agronomy, 2008)
The efficiency of base saturation (V%) method to correct an acid soil with high buffer chemical characteristic was studied under controlled conditions. Calcium carbonate (CaCO3) and magnesium carbonate (MgCO3) were used as lime at ratio of 3:1. Theoretical calculations were made to increase the values of V% to 40%, 60%, 80% and 100%. With the increasing values of V% there was an exponential reduction of Al saturation values. On the other hand, the pH values in H2O and in CaCl2 increased. The rates of CaCO3 and MgCO3 were enough and efficient to elevate the values of V% up to 60%. Over this V% value the rates were not efficient.